Pengaruh Model Pembelajaran Explicit Instruction terhadap Hasil Belajar Dasar-Dasar Ketenagalistrikan Siswa Kelas X Teknik Instalasi Tenaga Listrik SMKN 1 Merdeka Kabupaten Karo - Anugrah MS Kaban; Sukarman Purba; Veronika (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research aims to determine the effect of the Explicit Instruction learning model on student learning outcomes in basic electricity subjects. This type of research is a quasi-experimental research with the research design used being a pretest-posttest control group design. The population in the research carried out was all students in class X TITL SMKN 1 Merdeka, Karo Regency, consisting of two classes with a total of 72 students. The research sample consisted of two classes taken using random sampling techniques, namely class X TITL-1 with a total of 36 students as the experimental group taught using the Explicit Instruction model and class X TITL-2 with a total of 36 students as the control group taught using the by using expository learning. The instrument used in this research was a multiple choice test consisting of 35 questions. The research results showed that the average score obtained by students during the pre-test showed a significant change when students did the post-test, namely in the experimental class the pre-test was 44.17 and the post-test was 77.35, while in the control class the pre-test was 43.37. and post-test 71.14, so it is concluded that there is a positive influence of using the Explicit Instruction learning model on student learning outcomes.